Association Between Employee Dental Claims, Health Risks, Workplace Productivity, and Preventive Services Compliance. Issue 8 (August 2017) - Burton, Wayne N.; Chen, Chin-Yu; Li, Xingquan; Schultz, Alyssa B.
Abstract : Objective: This study examined differences in health risks and workplace outcomes among employees who utilized preventive dental services compared with other employees. Methods: A retrospective observational study of employees of a large financial services corporation, with data from health risk appraisal questionnaires, medical claims, pharmacy claims, and dental claims. Results: Employees with no dental claims were significantly more likely to have a variety of health risk factors (such as obesity and tobacco use), health conditions (such as diabetes), absenteeism, and lost on-the-job productivity, and were significantly less likely to be compliant with clinical preventive services compared with those with preventive dental claims. Conclusions: Employees with preventive dental claims had fewer health risks and medical conditions and better health and productivity measures. Study employees underutilized free dental care; employers should incorporate preventive dental care awareness into their worksite wellness programs.